Brainstem and Cerebellar Involvement in Ramsay Hunt Syndrome - Vijay Letchuman; Charles D. Donohoe (Case Reports in Otolaryngology)
We present a case of a 62-year-old Caucasian male with laryngeal cancer and Ramsay Hunt Syndrome otherwise known as herpes zoster oticus due to reactivation of the varicella zoster virus. Classic findings include the triad of ipsilateral facial paralysis, otic pain, and herpetic lesions in the sensory supply of the facial nerve. The common pathogenesis is associated with anterograde axonal reactivation of the varicella zoster virus in the geniculate ganglion. Unique features of our case include retrograde transaxonal spread of the varicella-zoster virus from the geniculate ganglion into the brainstem and cerebellum including involvement of the abducens nucleus, facial nucleus, middle cerebral peduncle, and inferior cerebellar peduncle. This presented as left facial paralysis, left sixth nerve palsy, horizontal diplopia to the left lateral gaze, profound truncal ataxia, and left-sided dysmetria. Clinical awareness that Ramsay Hunt syndrome may also involve the brainstem and cerebellum is critical in evaluating the clinical neurologic findings and expanding the diagnostic workup to include brain magnetic resonance imaging and cerebrospinal fluid analysis, including varicella zoster polymerase chain reaction. Encephalitis requires longer duration administration of high-dose intravenous acyclovir in conjunction with steroids. Delays in treatment are often associated with unsatisfactory outcomes with extensive residual deficits.